2012
DOI: 10.1289/ehp.1205436
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus (MRSA) Detected at Four U.S. Wastewater Treatment Plants

Abstract: Background: The incidence of community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) infections is increasing in the United States, and it is possible that municipal wastewater could be a reservoir of this microorganism. To date, no U.S. studies have evaluated the occurrence of MRSA in wastewater.Objective: We examined the occurrence of MRSA and methicillin-susceptible S. aureus (MSSA) at U.S. wastewater treatment plants.Methods: We collected wastewater samples from two Mid-Atlantic and two Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
68
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 27 publications
9
68
3
Order By: Relevance
“…The percentage resistance to ciprofloxacin in this study was 9.1% which is much lower when compared to the 63.1% in the aforementioned study in the United States. Resistance to both tetracycline and vancomycin in this present study was 22.7% and 9.1% respectively, which is comparable to the 14.3% and 0% resistance, respectively, as reported by Goldstein et al [38].…”
Section: Antibioticssupporting
confidence: 91%
See 2 more Smart Citations
“…The percentage resistance to ciprofloxacin in this study was 9.1% which is much lower when compared to the 63.1% in the aforementioned study in the United States. Resistance to both tetracycline and vancomycin in this present study was 22.7% and 9.1% respectively, which is comparable to the 14.3% and 0% resistance, respectively, as reported by Goldstein et al [38].…”
Section: Antibioticssupporting
confidence: 91%
“…The difference could be because of a better regulatory measure on abattoir management and disposal of wastes and wastewater in developed countries like Germany compared to a developing country like Nigeria. In a study carried out on strains of Methicillin Resistant Staphylococcus aureus (MRSA) obtained from wastewater treatment plants in the United States [38], it was reported that a percentage resistance of 98.8% was observed to oxacillin, and this was higher than the 63.3% resistance to the same antibiotics observed in this study. The percentage resistance to ciprofloxacin in this study was 9.1% which is much lower when compared to the 63.1% in the aforementioned study in the United States.…”
Section: Antibioticscontrasting
confidence: 69%
See 1 more Smart Citation
“…WWTPs receive direct input of resistant fecal and commensal bacteria from patients prescribed antibiotics. Most recently, methicillin-resistant Staphylococcus aureus (MRSA) was detected in the effluent of four U.S. WWTPs (Goldstein et al 2012), and bacteria resistant to clinically important antibiotics, including ciprofloxacin and vancomycin, have been found in the activated sludge (Nagulapally et al 2009). ARBs and ARGs may either decrease (i.e., via death and decay) or increase (i.e., via horizontal gene transfer and/or selective enrichment) through the treatment process.…”
Section: Issues and Recommendationsmentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant enterococci (VRE) have been detected in influent, activated sludge, secondary clarifier, post aeration, and effluent samples from U.S. WWTPs [14,15]. In addition, VRE have been detected at a U.S. reclaimed water spray irrigation site [16].…”
Section: Introductionmentioning
confidence: 99%